1988
DOI: 10.1115/1.3231358
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Formation Damage Pore Blocking Mechanisms

Abstract: The process of formation permeability damage due to solids movement and capture was quantitatively modeled by using principles of deep bed filtration and chemical reactions kinetics. The developed theory describes the pore blocking mechanism caused by particles from completion fluids (foreign particles invasion), as well as the mechanism of release and capture of rock fines (in-situ mobilization). For practical applications, this theory was used in the context of pattern recognition, i.e., to examine the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…However, particle jamming at the pore throats is more likely to occur because the area open for flow is small and the particles are more likely to coalesce when approaching the pore-throat constrictions. The present study confirms "porethroat plugging" as being the possible formation damage mechanism according to Wojtanowicz et al 8 and Civan 9 .…”
Section: Spe 106074supporting
confidence: 90%
See 2 more Smart Citations
“…However, particle jamming at the pore throats is more likely to occur because the area open for flow is small and the particles are more likely to coalesce when approaching the pore-throat constrictions. The present study confirms "porethroat plugging" as being the possible formation damage mechanism according to Wojtanowicz et al 8 and Civan 9 .…”
Section: Spe 106074supporting
confidence: 90%
“…Wojtanowicz et al 8 showed that the damage mechanism is controlled by the size of the particles. Therefore, the particle size experiments were conducted by taking snapshots of naphthenate soap particles under a light microscope at 200X magnification at different times.…”
Section: Particle Size Growth Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A quantitative model for the process of formation permeability alteration due to particle invasion and in-situ fine mobilization, using the principles of deep bed filtration and chemical reaction kinetics, has been proposed by Wojtanowicz et al (1988). Three mechanisms of formation pore blocking have been recognized and analyzed in this model with regard to particles invasion, which are gradual pore blocking, single pore blocking (screening), and cake formation (straining).…”
Section: Introductionmentioning
confidence: 99%
“…There are six reported modeling studies concerning the in-situ generation and migration of fines in porous media (Gruesbeck and Collins 1982;Khilar and Fogler 1987;Soo and Radke Clayton 1986;Wojtanowicz et al 1988;Civan et al 1990;Rochon et al 1996). In each of these studies simplified assumptions are made and the equations are solved to describe the reduction in permeability due to migration of the fine particles in porous media.…”
Section: Introductionmentioning
confidence: 99%